Hyoid Bone Syndrome and Dysphonia: Can Throat Pain Affect the Voice?. (23rd February 2021) - Rubin, Adam D.; Codino, Juliana; Bottalico, Pasquale; Parrish, Sheila; Jackson‐Menaldi, Cristina
Abstract : Objectives/Hypothesis: To investigate the relationship of throat pain and dysphonia. Study Design: Prospective cohort study. Methods: Forty‐five subjects presenting with hyoid bone syndrome (HBS) and dysphonia were asked to rate their pain on a numerical rating scale and complete the 10‐item Voice‐Related Quality of Life (V‐RQOL) questionnaire prior to and at 1‐week follow‐up after treatment with triamcinolone injection into the attachments to the affected greater cornu(s). Wilcoxon signed‐rank tests were applied to evaluate if the overall V‐RQOL scores, the physical functioning (PF) and social–emotional (SE) domain scores, and pain scores changed significantly after treatment. To evaluate how change in perceived pain affected V‐RQOL, the differences in the V‐RQOL, PF, and SE domain scores, and in pain scores were calculated for each subject. Three linear models were fit to the response variables, ΔV‐RQOL, ΔPF, and ΔSE, using ΔPain as a predicting variable. Results: V‐RQOL, PF, and SE domain scores, and pain scores all improved significantly with treatment. A bigger decrease in the pain score led to a bigger increase in V‐RQOL and domain scores, with slopes varying between −1.1 and −1.4. The PF domain scores showed the greatest improvement with decrease in pain scores. Conclusions: Effective treatment of HBS led to improvement in patients' voice complaints, suggesting that throat pain may have a direct effect on voice. This may be related to compensatory perilaryngeal adjustments patients make when speaking with a "guarding" effect when they have throat pain. Level of Evidence: IV (Cohort study) Laryngoscope, 131:E2303–E2308, 2021